Peran Guru Pendidikan Agama Islam dalam Mengatasi Siswa Kelas IX yang Merokok dan Terlambat Masuk Kelas di SMP Negeri 1 Kualuh Leidong - Sagala, Nurhikmah; Padang, Ramlan; Adawiyah, Rabiatul (ANWARUL, 2024)
The purpose of this study is to identify the factors causing 9th-grade students to smoke and arrive late to class at SMP Negeri 1 Kualuh Leidong, to analyze the role and influence of Islamic Religious Education (PAI) teachers in addressing these issues, and to explore the solutions provided by PAI teachers to overcome smoking and tardiness among these students. This research employs a quantitative method, with a sample size of 56 students. Data collection was conducted using questionnaires, and data analysis was performed using statistical methods through SPSS. The results of this study indicate that the internal factor leading students to smoke is their curiosity and desire to try it, while external factors include peer influence. Tardiness in attending class is attributed to internal factors such as laziness, and external factors such as long distances and traffic congestion. The role of Islamic Religious Education teachers in handling 9th-grade students who smoke and are frequently late to class involves educating, mentoring, and motivating students to understand and practice Islamic teachings. This role significantly impacts addressing these issues, as evidenced by a t-value of 28.000, which is greater than the critical t-value of 1.673 (28.000 > 1.673). The influence of the independent variable (X) on the dependent variable (Y) is 39.6%. The solutions provided by Islamic Religious Education teachers include advising and guiding students, as well as imposing disciplinary actions on those who violate school rules.